Residents' concerns and attitudes towards municipal solid waste management: opportunities for improved management. (8th May 2019) - Baawain, Mahad Said; Al-Mamun, Abdullah; Omidvarborna, Hamid; Al-Mujaini, Fatma; Choudri, B.S.
Rapid urbanisation, industrial and economic growth have caused a tremendous increase in the municipal solid waste (MSW) generation in developing countries. Therefore, solid waste management (SWM) has become a serious issue among the developing countries. Aiming to understand residents' knowledge, awareness and concerns towards MSW and SWM, this study intended to identify concerns and attitudes towards solid waste generation and management in Muscat, Oman. Therefore, a survey study was carried out to solicit the opinion of the residents and to get primary data about solid waste generation and management in Muscat. The generation of MSW was assessed based on different socioeconomic aspects, such as gender, education level, age and working status. The majority of the respondents had positive attitudes towards source reduction, separation and recycling attitudes and practices. The public had the objection to burn solid waste, including incineration (80%) and strong opinion to have proper regulations/legislations towards SWM (88%).